The relationship between diabetes and surgical site infection following coronary artery bypass graft surgery in current-era models of care. (October 2021) - Cheuk, N.; Worth, L.J.; Tatoulis, J.; Skillington, P.; Kyi, M.; Fourlanos, S.
Summary: Background: Although diabetes is a recognized risk factor for postoperative infections, the seminal Portland Diabetic Project studies in cardiac surgery demonstrated intravenous insulin infusions following open-cardiac surgery achieved near normal glycaemia and decreased deep sternal wound infection to similar rates to those without diabetes. Aim: We sought to examine a contemporary cohort of patients undergoing coronary artery bypass graft surgery (CABGS) to evaluate the relationship between diabetes, hyperglycaemia and risk of surgical site infection (SSI) in current-era models of care. Methods: Consecutive patients who underwent CABGS between 2016 and 2018 were identified through a state-wide data repository for healthcare-associated infections. Clinical characteristics and records of postoperative SSIs were obtained from individual chart review. Type 2 diabetes (T2D), perioperative glycaemia and other clinical characteristics were analysed in relation to the development of SSI. Findings: Of the 953 patients evaluated, 11% developed SSIs a median eight days post CABGS, with few cases of deep SSIs (<1%). T2D was evident in 41% and more prevalent in those who developed SSIs (51%). On multivariate analysis T2D was not significantly associated with development of SSI (odds ratio (OR) 1.35; P =0.174) but body mass index (BMI) remained a significant risk factor (OR 1.07, P <0.001). In patients with T2D, perioperative glycaemia was not significantly associated with SSI. Conclusion: In a specialist cardiac surgery centre using perioperative intravenous insulin infusions and antibiotic prophylaxis, deep SSIs were uncommon; however, approximately one in 10 patients developed superficial SSIs. T2D was not independently associated with SSI yet BMI was independently associated with SSI post CABGS.